Estrategias metodológicas colaborativas para mejorar el aprendizaje de estudios sociales en los estudiantes de cuarto grado “A” de la unidad educativa José Ingenieros del cantón Loja, periodo 2017- 2018 - Avila Sanchez, Dennis Eliana (2018)
The research Collaborative methodological strategies to improve the learning of Social Studies in the fourth grade students "A" of the José Ingenieros Educational Unit of the Loja canton, period 2017-2018; Its general objective is to employ collaborative methodological strategies through pedagogical workshops to improve the learning of Social Studies in the students of the fourth grade "A" of the José Ingenieros Educational Unit of the Loja canton, period 2017-2018. The type of study is descriptive, quasiexperimental design; applied methods the scientific, descriptive, inductive, deductive, analytical, synthetic, statistical; the techniques: observation, survey, interview; instruments: observation sheet, questionnaire and question bank; procedures developed based on the theoretical foundation, diagnosis, proposal, application and validation of the alternative. As a result, the teacher is unaware of the conception and management of collaborative methodological strategies, nullifying their application. Population investigated: one teacher and 30 students. The teacher presents constant traditional practices reverberating in the learners' learning.